Increased frequency of circulating regulatory T cells in patients with acute cerebral hemorrhage. (30th March 2015) - Shi, Lijin; Qin, Jie; Song, Bo; Wang, Qing Mei; Zhang, Rui; Liu, Xinjing; Liu, Yutao; Hou, Haiman; Chen, Xiulan; Ma, Xun; Jiang, Chenyang; Sun, Xiao; et al.
Highlights: The frequency of circulating Tregs increased significantly post human ICH. More increase of Tregs in severe patients than that in less-severe patients. Both TGF-β and IL-10 in plasma were elevated in ICH patients. Tregs might play an important role in ICH-induced immunoreactions and injuries. Abstract: Cerebral hemorrhage (ICH) is a serious stroke subtype, currently lacking effective treatment. Recent research has shown that CD4 + CD25 + FOXP3 + regulatory T cells (Tregs) play a key role in the immune response of ischemic stroke. However, Tregs in human hemorrhagic stroke are poorly investigated. In this study, a total of 90 ICH patients and 60 healthy controls were recruited. The frequency of circulating Tregs, plasma levels of TGF-β and IL-10, and the severity of neural dysfunction in ICH patients were investigated at different time points post ICH. We found that the peripheral frequency of Tregs in ICH patients was significantly increased, accompanied by boosted activated T cells. Importantly, the elevation of circulating Tregs in patients with severe dysfunction was much higher than that in less-severe patients, suggesting that disease severity affects circulating Tregs to exert regulatory function. Furthermore, both TGF-β and IL-10 that are related to the function of Tregs, were also increased in the peripheral blood of ICH patients. Our results demonstrate that Tregs-mediated immune imbalance might affect the development and severity of ICH, and suggest that Tregs may be used as tools and targets of cellular immunotherapy to effectively treat acute hemorrhagic stroke.